The Japanese fortune calendar - Chiba, Reiko (Charles E. Tuttle, 1965)
There are three phases in a person's life span, and the fortune of each phase is clearly defined. Japanese fortunetellers say that are able to determine the events for all of these phases and advise or counsel alternative courses to avoid misfortune.